The Impact of Mental Illness Stigma on Psychiatric Emergencies - da Silva, Antônio Geraldo; Baldaçara, Leonardo; Cavalcante, Daniel A.; Fasanella, Nicoli Abrão; Palha, Antônio Pacheco (Frontiers in Psychiatry, 2020)
Psychiatric emergencies are severe behavioral changes secondary to worsening mental illness. Such situations present a risk to the patient and other people, so they need immediate therapeutic intervention. They are associated with feelings of fear, anger, prejudice, and even exclusion. The attitudes of professionals and factors related to the workplace culture in health can help to perpetuate stereotypes and interfere with the quality of care. Stigma has undesirable consequences in patients with mental disorders. Certain measures can reduce stigma and provide a more dignified way for patients to recover from the crisis. This article aims to discuss the causes of stigma, ways of dealing with it, and achievements that have been made in psychiatric emergency care settings.